Karakterisasi Dan Potensi Pemanfaatan Limbah Rumah Makan Sebagai Energi Terbarukan - Fikri Julian; David Andrio; Lita Darmayanti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Food Waste contains high concentrations of organic pollutants. The high organic concentration in food waste makes it suitable reused as an energy source. This study aims to investigate the characteristics of food waste and analyze the potential of food waste. The results of this study indicate the concentration of COD in food waste 58.514 mg / L, oil and fat amounting to 2.340 mg / L and pH 3,4. With high organic concentration then food waste can be utilized as bioethanol and biogas. Keywords: Food Waste